The significance of network management system in school labs - Abdul Aziz S.R.; Ibrahim M.; Sauti M.S. (Penerbit UTM Press, 2023)
This preliminary study is intended to identify the significance of network management system (NMS) in the school computer lab. It was found that most of ICT teachers are not familiar with network management system; majority has yet to attend course pertaining to network management system. In this study, 15 ICT teachers from 15 different schools in Selangor were given a questionnaire that focuses on Demographic Data and the School Computer Lab information. This study discovered that there is no standard Network Management System placed in school computer lab in Selangor. Issues such as server failure, malfunction internetworking devices and slow network access prompts the new user friendly NMS, intended specifically for school ICT teachers. 2015 Penerbit UTM Press. All rights reserved.